Decreasing prevalence of no known major risk factors for cardiovascular disease among Mississippi adults, Mississippi Behavioral Risk Factor Surveillance System, 2001 and 2009 - Vincent L. Mendy; Rodolfo Vargas; Lamees El-sadek; Vanessa L. Short (BMC, 2016)
Abstract Background Cardiovascular disease (CVD) is the leading cause of death in Mississippi. However, the prevalence of no known CVD risk factors among Mississippi adults and the change of prevalence in the past 9 years have not been described. We assess changes in prevalence of no known CVD risk factors during 2001 and 2009. Methods Prevalence of high blood pressure, high cholesterol, diabetes, physical inactivity, smoking, and obesity were investigated. Survey respondents who reported having none of these factors were defined as having no known CVD risk factors. Differences in prevalence and 95% confidence intervals were determined using t-test analysis. Results Overall, age-standardized prevalence of having no known CVD risk factors significantly decreased from 17.3% in 2001 to 14.5% in 2009 (p = 0.0091). The age-standardized prevalence of no known CVD risk factors were significantly lower in 2009 than in 2001 among blacks (8.9% vs. 13.2%, p = 0.008); males (13.5% vs. 17.9%, p = 0.0073); individuals with a college degree (25.2%, vs. 30.8%, p = 0.0483); and those with an annual household income of $20,000-$34,999 (11.6% vs. 16.9%, p = 0.0147); and $35,000-$49,999 (15.2% vs. 23.3%, p = 0.0135). Conclusion The prevalence of no known CVD risk factors among Mississippi adults significantly decreased from 2001 to 2009 with observed differences by race, age group, sex, and annual household income.